Psychometric properties of the Irish Management Standards Indicator Tool. (7th December 2016) - Boyd, S.; Kerr, R.; Murray, P.
Abstract : Background: Work Positive is Ireland's national policy initiative to control work-related stress. Since the introduction of the UK Health and Safety Executive's Management Standards (MS) in 2004, a number of studies have been undertaken to assess the potential adaptation of the MS framework within Ireland. Aims: To investigate the dimensionality, reliability and validity of the Irish version of the MS Indicator Tool (ROI-MSIT). Methods: Between February 2011 and June 2014, we collected data from a wide range of public and private sector organizations that used the ROI-MSIT. In addition to the ROI-MSIT, respondents completed the WHO-Five Well-being Index (WHO-5). Exploratory factor analysis (EFA) was used to determine whether the ROI-MSIT maintained the structure of the UK instrument. The internal consistency of the ROI-MSIT was also assessed to determine its reliability, while its criterion-related validity was explored through correlation analysis with the WHO-5. Results: Data were collected from 7377 participants. The factor structure of the ROI-MSIT consisted of six factors; the Demands, Control, Peer Support, Relationships and Role factors were equivalent to the original UK factors. Like the Italian version, a principal factor emerged that combined the Manager Support and Change domains. Cronbach's alpha scores ranged from 0.75 to 0.91. Finally, the ROI-MSIT's subscales and WHO-5 were positively correlated ( r = 0.42–0.59, P < 0.001). Conclusions: The ROI-MSIT is reliable and valid, with a factor structure similar to the original UK instrument and the Italian MSIT. Further psychometric evaluation of the ROI-MSIT is recommended.